The impact of the EC's agricultural policy on its trade with developing countries - Karl-Heinz Beißner; Hans-Rimbert Hemmer (Intereconomics, 1981)
The European Community has frequently been blamed for impairing, through its highly protectionist agricultural policy, the development chances of Third World countries. Our article analyses whether, and to what extent, this reproach is justified.
Keywords: 330; European Community